2013
DOI: 10.1089/scd.2012.0703
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Using Cancer Stem Cell Markers in Isolating and Characterizing Liver Cancer Stem Cells

Abstract: Recent evidence suggests that a subset of hepatocellular carcinomas (HCCs) are derived from liver cancer stem cells (LCSCs). In order to isolate and characterize LCSCs, reliable markers that are specific to these cells are required. We evaluated the efficacy of a range of cancer stem cell (CSC) markers in isolating and characterizing LCSCs. We show that the most widely used CSC markers are not specific to LCSCs. By western analysis, protein expression of the common markers showed no significant difference betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…1C). Altogether, these results indicated that CD133 and EpCAM markers were convenient for identifying cells that have cancer stem cell like features in epithelial-like HCC cell lines and were compatible with the literature (11,12).…”
Section: Isolated Cd133+/epcam+ Cells Display Cancer Stem Cell Characsupporting
confidence: 86%
“…1C). Altogether, these results indicated that CD133 and EpCAM markers were convenient for identifying cells that have cancer stem cell like features in epithelial-like HCC cell lines and were compatible with the literature (11,12).…”
Section: Isolated Cd133+/epcam+ Cells Display Cancer Stem Cell Characsupporting
confidence: 86%
“…42 With regard to the controversial outcome of using signal biomarkers to identify and isolate CSCs, a growing pool of data suggested that combinations of multiple biomarkers might be the more effectual means of identifying CSCs and prognostic assessment in HCC. [41][42][43] Considering PTEN is a vital upstream initiator and key activation manager of the PTEN/AKT/mTOR pathway, we opted for the combination of PTEN and LCSC markers to evaluate prognosis. We found that HCC patients with PTEN À /CD133 + or PTEN À /EpCAM + expression had a high risk of recurrence and poor prognosis, compared to the other combinations.…”
Section: Discussionmentioning
confidence: 99%
“…T‐ICs have been implicated in recurrence and therapeutic resistance. Several recent studies support this hypothesis and have revealed that epithelial cell adhesion molecule (EpCAM) + and label‐retaining HCC cells are more resistant to sorafenib treatment . Recently, we have identified CD47 as a novel therapeutic target for elimination of liver T‐ICs .…”
mentioning
confidence: 81%